Analisis Persepsi Keadilan Pajak di Kalangan Mahasiswa Universitas 17 Agustus 1945 Surabaya Pasca Kenaikan Tarif PPN 12% - Nor Hasan; Maria Trivonia Somi; Nur Nur; Nailah Nur Salma; Cindy Viorensia Putri (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
This study aims to explore the views of students at the University of 17 August 1945 (UNTAG) Surabaya regarding the increase in the Value-Added Tax (VAT) rate to 12%, which took effect on January 1, 2025. This policy shift is part of a broader tax reform aimed at strengthening Indonesia's fiscal capacity, yet it has raised concerns about its fairness and impact on lower-income groups, particularly students. Using a descriptive qualitative method, data were collected via open-ended questionnaires from 50 active students between May and June 2026. Thematic analysis was conducted using the multidimensional framework by Marshall et al. (2023), which encompasses aspects of distributive, procedural, retributive, and interactional justice. The research findings reveal that perceptions of distributive injustice were the most frequently cited in the responses (72%), followed by the impact on consumption behavior (68%) and dissatisfaction with the process (64%). Trust in the government was found to play a significant moderating role in shaping students' acceptance of the policy, while perceived weaknesses in interactional justice, particularly regarding tax authority communication, further reinforced negative perceptions. These findings underscore the importance of implementing more open and transparent communication strategies and involving the public, especially younger generations, in the formulation of tax policy. Strengthening these dimensions of fairness is expected to increase public support for and compliance with changes in the tax system, while also contributing new empirical insight into student perceptions of taxation policy in the Indonesian context.